Semantic segmentation of substation tools using an improved ICNet network - Guozhong Liu; Qiongping Tang; Changnian Lin; An Xu; Chonglong Lin; Hao Meng; Mengyu Ruan; Wei Jin (Electronic Research Archive)
In the field of substation operation and maintenance, real-time detection and precise segmentation of tools play an important role in maintaining the safe operation of the power grid and guiding operators to work safely. To improve the accuracy and real-time performance of semantic segmentation of substation operation and maintenance tools, we have proposed an improved, light-weight, real-time, semantic segmentation network based on an efficient image cascade network architecture (ICNet). The network uses multiscale branches and cascaded feature fusion units to extract rich multilevel features. We designed a semantic segmentation and purification module to deal with redundant and conflicting information in multiscale feature fusion. A lightweight backbone network was used in the feature extraction stage at different resolutions, and a recursive gated convolution was used in the upsampling stage to achieve high-order spatial interactions, thereby improving segmentation accuracy. Due to the lack of a substation tool semantic segmentation data set, we constructed one. Training and testing on the data set showed that the proposed model improved the accuracy of tool detection while ensuring real-time performance. Compared with the currently popular semantic segmentation network, it had better performance in real-time and accuracy, and provided a new semantic segmentation method for embedded platforms.